PENGARUH KULTUR MEDIA PERTUMBUHAN MAGGOT BSF (Hermetia illucens) SEBAGAI BIOKONVERSI PAKAN AYAM BURAS FASE STARTER - Haryanto, Sugeng; Hoda, Abdurahman (Jurnal Pertanian Khairun, 2024)
This study aims to determine the effect of various types of growth media maggot from banana waste (Musa paradisiaca) taken from traditional markets on the performance of starter phase local chicken with several parameters measured, namely maggot biomass, daily weight gain of local chicken, feed consumption and feed conversion chicken starter phase. This research was carried out experimentally with four treatments that were tried namely basal ration (P0), basal ration added maggot from banana stem culture media (P1), basal ration added maggot with banana weevil (P2) culture and basal ration added maggot with banana skin culture media (P3). The results showed that the banana waste both in the stem, tuber and skin parts had a very significant effect (p 0.01) with sig values. 0.009 on maggot larvae biomass in the first week of weighing. Whereas the 2nd and 3rd weeks have a significant influence on the value of sig. 0.023 and 0.045 (p 0.05). The use of banana peels as a culture medium gives the best effect on the growth of BSF maggot larvae compared to banana weevil and gedebog. Maggot BSF larvae using banana stem culture media (P3) in the ration gave a good influence on the daily weight gain and consumption of starter phase rations. Whereas all treatments had the same effect on feed conversion.Keywords: Maggot, Banana waste, Growth, local chicken